Prenatal yoga [videorecording (DVD)] - Landon, Ted; Rea, Shiva (Gaiam, 2003)
Instructor Shiva Rea demonstrates a series of stretches and strength-building exercises that address the specific needs of a changing body. This workout focuses on comfort and relaxation while increasing energy and stamina.